An Analysis of Management Buy-out Failure in Recession - Huo, Huan (2009)
The UK buy-out market went down in the last quarter of 2008 with a significant reduction of deal numbers and deal values. Besides, the exit market has been difficult through 2008 with no buy-out IPOs but large proportion of receiverships. Therefore buy-out failure attracts interest and it would be worthwhile to identify factors that leads to or predicts a failure, particularly in a recessional condition.